Pengawasan dan Penegakan Hukum terhadap Sertifikasi dan Labelisasi Halal Produk Pangan - KN Sofyan Hasan (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The primary problem in this study is how to law enforcement and the protection of consumer's rights against the certification and labeling of halal products according to UUJPH. The second problem to consider is the factors that causing young enterpreneurs to delay certification and halal product labeling on their products. This is a normative juridical research with a complementary juridical empirical data. The study points out that: first, until now there has been no law enforcement and no collective protection of consumer rights on the certification and labeling of halal products. To complicate matters, there is lack of coordination between ministries and agencies by MORA RI. Second, some of the factors that cause the enterpreneurs to delay halal certification on their products are the facts  that: i) UUJPH cannot be implemented operationally because the Government Regulation (PP) has not been issued; ii) BPJPH which is the mandate of UUJPH has not been established; iii) Business actors find it difficult to certify some kinds of their products, such as pharmaceutical products  since  the raw materials are  imported from abroad; iv) There is a reatively poor public awareness of  consumers of halal products  since they do not prioritize halal factor in selecting and purchasing a product.